2012
DOI: 10.1177/0021943612446750
|View full text |Cite
|
Sign up to set email alerts
|

Man and Woman Talk in Indian Organizations: Grammatical and Syntactical Similarities

Abstract: The article examines grammatical and syntactical forms in reported speeches of men and women in the Indian work environment. Until recently, there has been little or no study on the linguistic performance across genders in the Indian setting. However, the recent advent of women in the organizations indicates that an understanding of the linguistic similarities or variances is required and will aid collaborative communication. Based on an empirical study, the article posits that linguistic variances in the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…To date, intra-and intercultural qualitative research on workplace interactions inspired by ethnography and discourse analysis have shown the value of emic knowledge as gained from the anal-ysis of real-life work practices. Such insights could be usefully fed into the CCM curriculum alongside students' preparation for and execution of ethnographic projects (e.g., Salvi & Tanaka, 2011;Koester, 2004;Drew & Heritage, 1992;Yamada, 1992;Dhanania & Gopakumaran, 2005;Hong, Easterby-Smith, & Snell, 2006;Boden, 1994;Bargiela-Chiappini & Harris, 1997;Tanaka & Bargiela-Chiappini, 2011;Hanford, 2010;Nair-Venugopal, 2006;Paramasivam, 2007;Fujo, 2004;Tanaka, 2011;Chakorn, 2006;Kaul, 2012;Yotsukura, 2003;Zhu, 2005).…”
Section: Situated Curriculum For Ccm Learningmentioning
confidence: 99%
“…To date, intra-and intercultural qualitative research on workplace interactions inspired by ethnography and discourse analysis have shown the value of emic knowledge as gained from the anal-ysis of real-life work practices. Such insights could be usefully fed into the CCM curriculum alongside students' preparation for and execution of ethnographic projects (e.g., Salvi & Tanaka, 2011;Koester, 2004;Drew & Heritage, 1992;Yamada, 1992;Dhanania & Gopakumaran, 2005;Hong, Easterby-Smith, & Snell, 2006;Boden, 1994;Bargiela-Chiappini & Harris, 1997;Tanaka & Bargiela-Chiappini, 2011;Hanford, 2010;Nair-Venugopal, 2006;Paramasivam, 2007;Fujo, 2004;Tanaka, 2011;Chakorn, 2006;Kaul, 2012;Yotsukura, 2003;Zhu, 2005).…”
Section: Situated Curriculum For Ccm Learningmentioning
confidence: 99%
“…The crux of this question lay in the language practices and the ways in which they reflected and enacted concepts of status and power. Drawing on my own cultural upbringing in a South Asian context, I presumed that the Malayali families would be based on the Indian patriarchal system within which authority and status are assigned on the basis of gender and generation (Kaul 2012). Accordingly, within a nuclear family unit in which a married heterosexual couple are of the same generation, the father would become the head of the household owing to his gender.…”
Section: Introductionmentioning
confidence: 99%